2022
DOI: 10.6007/ijarbss/v12-i6/14220
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of The Effectiveness of Gamification Module for Arabic Language in Primary School

Abstract: The teaching and learning of Arabic in primary schools was officially introduced in the Malaysian education system through the j-QAF program (Jawi, al-Quran, Arabic, and fardhu ain) beginning in 2005. Therefore, teachers need to use a centralized approach and strategy. Gamification is an alternative approach to strengthening students' knowledge, cultivating attitudes, increasing motivation as well as improving their achievement and language skills. The implementation of gamification can be through online appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this regard, three concepts were common in the review. Gamification refers to the integration of games into a non-gamified environment such as a classroom or other learning environment (Kotob and Ibrahim, 2019;Riwanda et al, 2021;Bin Jaafar and Yusoff, 2022;Abdelhamid et al, 2023). Game-based strategies involve integrating phone or computer-based games into the learning process (Ju and Adam, 2018;Ghani et al, 2019;Al Hejaili and Newbury, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, three concepts were common in the review. Gamification refers to the integration of games into a non-gamified environment such as a classroom or other learning environment (Kotob and Ibrahim, 2019;Riwanda et al, 2021;Bin Jaafar and Yusoff, 2022;Abdelhamid et al, 2023). Game-based strategies involve integrating phone or computer-based games into the learning process (Ju and Adam, 2018;Ghani et al, 2019;Al Hejaili and Newbury, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…All six studies focused on game-based Arabic language learning, but the target group and research design of the studies were different depending on the nature. They followed pre-test/post-test design (i.e., 3/15) (Kotob and Ibrahim, 2019;Ritonga et al, 2022;Abdelhamid et al, 2023), quantitative approach (i.e., 8/15) (Sahrir and Alias, 2011;Yan Mei et al, 2018;Azmi and Zakaria, 2020;Putri et al, 2021;Riwanda et al, 2021;Bin Jaafar and Yusoff, 2022;Ismath et al, 2022;Noor et al, 2023), content analysis (i.e., 1/15) (Al-Bulushi and Al-Issa, 2017), experiment (i.e., 3/15) (Kenali et al, 2019;Al Hejaili and Newbury, 2023;Mazer and Al-Ajlouni, 2023), and qualitative approach (i.e., 1/15) (Ghani et al, 2019). The details of the research design are also shown in Figure 3.…”
Section: Focus Aim and Approachmentioning
confidence: 99%
See 2 more Smart Citations